Immediate Versus Staged Complete Revascularization for Patients With ST‐Segment–Elevation Myocardial Infarction and Multivessel Disease: A Network Meta‐Analysis of Randomized Trials - Ayman Elbadawi; Mohamed Hamed; Mohamed Gad; Sheref A. Elseidy; Mohamed Barghout; Hani Jneid; Mamas A. Mamas; Fernando Alfonso; Islam Y. Elgendy (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background The comparative outcomes with immediate, staged in‐hospital, and staged out‐of‐hospital complete revascularization for patients with ST‐segment–elevation myocardial infarction and multivessel disease remain unclear. Methods and Results An electronic search of MEDLINE, SCOPUS, and Cochrane databases was performed through August 2023 for randomized trials evaluating immediate, staged in‐hospital, and staged out‐of‐hospital complete revascularization for patients with ST‐segment–elevation myocardial infarction and multivessel disease. The primary outcome was major adverse cardiac events (MACEs). The final analysis included 9 trials with 4270 patients. The weighted follow‐up duration was 13.8 months. On pairwise meta‐analysis, there were no statistically significant differences between immediate versus staged nonculprit percutaneous coronary intervention (PCI) in MACEs (odds ratio, 0.79 [95% CI, 0.54–1.16]). Network meta‐analysis showed that there was no statistically significant difference in MACEs with staged in‐hospital nonculprit PCI (odds ratio, 1.29–[95% CI, 0.91–1.82]) compared with immediate nonculprit PCI, while there were higher odds of MACEs with out‐of‐hospital nonculprit PCI (odds ratio, 1.67–[95% CI, 1.21–2.30]) compared with immediate nonculprit PCI. Compared with immediate nonculprit PCI, there were higher odds of ischemia‐driven repeat revascularization with staged out‐of‐hospital nonculprit PCI (odds ratio, 2.26–[95% CI, 1.37–3.72]), but not with in‐hospital staged nonculprit PCI. There were no significant differences for the other outcomes among the 3 strategies. Conclusions Among patients with ST‐segment–elevation myocardial infarction with multivessel disease, an immediate nonculprit PCI approach was associated with similar clinical outcomes to the staged nonculprit PCI approach. The staged out‐of‐hospital nonculprit PCI approach was associated with a higher incidence of MACEs compared with the other strategies, which was driven by higher risk for ischemia‐driven repeat revascularization.